New biologics and small molecules in inflammatory bowel disease: an update. (May 2019) - Sabino, João; Verstockt, Bram; Vermeire, Séverine; Ferrante, Marc
Inflammatory bowel disease (IBD) is a spectrum of immune-mediated inflammatory disorders with a complex multifactorial pathogenesis, where different pathways may predominate in different individuals. This complexity will most likely require a panoply of drugs targeting different pathways if one wants to treat to steroid-free sustained remission and mucosal healing. Presently, the mainstay of medical management of IBD is based on 5-aminosalicylates, corticosteroids, thiopurines, methotrexate, antitumor necrosis factor, anti-alpha4 beta7 (α4β7) integrin and anti-interleukin (IL)-12/IL-23 therapies. The discovery of new pathways involved in the pathogenesis of IBD resulted in new drugs targeting Janus kinase/signal transducers and activators of transcription, IL-6, spingosine-1-phosphate, and phosphodiesterase 4, among others. These new therapies might result in more advantageous safety profiles. Several of these new drugs have already been successfully tested in other inflammatory disorders, such as psoriasis or rheumatoid arthritis. In this review, evidence from phase II and phase III randomized controlled clinical trials in patients with IBD involving new biologicals and small molecules are summarized.